Sustained high‐fat diet modulates inflammation, insulin signalling and cognition in mice and a modified xenin peptide ameliorates neuropathology in a chronic high‐fat model. Issue 5 (11th February 2018) - Denver, Paul; Gault, Victor A.; McClean, Paula L.
Abstract : Aims: To demarcate pathological events in the brain as a result of short‐term to chronic high‐fat‐diet (HFD) feeding, which leads to cognitive impairment and neuroinflammation, and to assess the efficacy of Xenin‐25[Lys(13)PAL] in chronic HFD‐fed mice. Methods: C57BL/6 mice were fed an HFD or a normal diet for 18 days, 34 days, 10 and 21 weeks. Cognition was assessed using novel object recognition and the Morris water maze. Markers of insulin signalling and inflammation were measured in brain and plasma using immunohistochemistry, quantitative PCR and multi‐array technology. Xenin‐25[Lys(13)PAL] was also administered for 5 weeks in chronic HFD‐fed mice to assess therapeutic potential at a pathological stage. Results: Recognition memory was consistently impaired in HFD‐fed mice and spatial learning was impaired in 18‐day and 21‐week HFD‐fed mice. Gliosis, oxidative stress and IRS‐1 pSer 616 were increased in the brain on day 18 in HFD‐fed mice and were reduced by Xenin‐25[Lys(13)PAL] in 21‐week HFD‐fed mice. In plasma, HFD feeding elevated interleukin (IL)‐6 and chemokine (C‐X‐C motif) ligand 1 at day 34 and IL‐5 at week 10. In the brain, HFD feeding reduced extracellular signal‐regulated kinase 2 (ERK2), mechanistic target of rapamycin (mTOR), NF‐κB1, protein kinase C (PKC)θ and Toll‐like receptor 4 (TLR4) mRNA at week 10 and increased expression of glucacon‐like peptide‐1 receptor, inhibitor of NF‐κB kinase β, ERK2, mTOR, NF‐κB1, PKCθ and TLR4 at week 21, elevations that were abrogated by Xenin‐25[Lys(13)PAL]. Conclusions: HFD feeding modulates cognitive function, synapse density, inflammation and insulin resistance in the brain. Xenin‐25[Lys(13)PAL] ameliorated markers of inflammation and insulin signalling dysregulation and may have therapeutic potential in the treatment of diseases associated with neuroinflammation or perturbed insulin signalling in the brain.